Screening for Latent Infections Among Users of High-Risk Immunosuppressants: A Cross-Sectional Analysis From the Veterans Health Administration Healthcare System. Issue 1 (17th January 2023) - Schmajuk, Gabriela; Montgomery, Anna; Tarasovsky, Gary; Li, Jing; Hauser, Ronald G.; Rozenberg-Ben-Dror, Karine; Whooley, Mary A.
Abstract : Objectives: Guidelines recommend screening for latent hepatitis B virus (HBV), hepatitis C virus (HCV), and tuberculosis (TB) before initiating biologics or targeted synthetic disease-modifying antirheumatic drugs (b/ts DMARDs) to avoid reactivation of life-threatening infections. The extent to which such screening occurs in the national Veterans Health Administration (VA) healthcare system is unknown. Methods: Using data from the Veterans Affairs' (VA) Corporate Data Warehouse, we performed a cross-sectional analysis of veterans receiving b/ts DMARDs between October 1, 2017, and September 30, 2019. We calculated the proportion of patients with screening completed for latent HBV, HCV, and TB between October 1, 1999 and September 30, 2019. Patient characteristics associated with complete screening were evaluated using mixed-effects multivariate logistic regression models. We also examined facility-level factors associated with high versus lower performance. Results: A total of 51, 764 unique patients from 129 VA facilities received b/ts DMARDs from 2017 to 2019. Of these, 63% had complete screening. Among the 11, 006 patients identified as new users, 64% had complete screening. Higher screening rates were observed among Hispanic/Latinx and Black/African American patients, users of B-cell therapies, and patients who had seen oncology subspecialists. Substantial variation was observed across facilities, with complete screening ranging from 13% to 98% of patients. Higher screening rates were associated with highly complex, urban, and higher-volume facilities. Conclusions: Approximately two-thirds of veterans taking b/ts DMARDs have received guideline-recommended screening for HBV, HCV, and TB, but substantial facility variation was observed. Performance measures, robust multidisciplinary workflows, and electronic health record–based tools to feed information back to providers may improve screening rates for low-performing facilities.